Performance of water-based liquid scintillator - Beznosko, D.; Diwan, M.; Hans, S.; Jaffe, D.; Kettell, S.H.; Rosero, R.; Themann, H.; Viren, B.; Worcester, E.; Yeh, M.; Zhang, C. (Nazarbayev University, 2013)
In order to successfully use both detection techniques with the WbLS, a minimum of about 100 optical photons per MeV of deposited energy should be produced. A test was carried out with the high-energy proton beam using 2 different WbLS formulations to assess the availability of such a light yield (LY) for this material at beam energy of 475MeV.
Keywords: first research week; innovative scientific research; Water-based Liquid Scintillator